Artificial Intelligence for Santri; Building a Faithful Technological Generation - Rosi, Fathor; Agus Nu'man; Naser Ali Abdulghani (Yayasan Avicenna, 2024)
This study aims to analyze the application of artificial intelligence (AI) in learning in Islamic boarding schools and how this technology can play a role in building a generation of intelligent and faithful students. The approach used in this study is qualitative with a case study type. The subjects of the study included Islamic boarding school leaders, educators, students, technology managers, and alumni of Islamic boarding schools. Data collection techniques were carried out through in-depth interviews, observation, and documentation, while data analysis was carried out using data reduction techniques, data presentation, and conclusion. The results of this study indicate that the use of AI in learning in Islamic boarding schools can improve students' understanding of the material, especially in mastering yellow books and religious material, while maintaining Islamic values. This technology also supports the development of digital literacy for students, without ignoring aspects of morality and spirituality. This finding implies that the integration of AI in Islamic boarding schools can create a generation of students who are better prepared to face digital challenges, but still adhere to strong religious teachings.